Comments on: Further studies of Bolivian crocidolite-Part IV: Fibre width, fibre drift and their relation to mesothelioma induction: Preliminary findings, by Ilgren EB, van Orden DR, Lee RJ, Kamiya YM, Hoskins JA. - Corrado Magnani; Francesco Barone-Adesi; Annibale Biggeri; Pietro Comba; Paola Dalmasso; Daniela Marsili; Milena Maule; Franco Merletti; Dario Mirabelli; Roberto Pasetto; Benedetto Terracini (Epidemiology, Biostatistics and Public Health)
Comments on: Further studies of Bolivian crocidolite-Part IV: Fibre width, fibre drift and their relation to mesothelioma induction: Preliminary findings, by Ilgren EB, van Orden DR, Lee RJ, Kamiya YM, Hoskins JA.